Overcoming Perfectionism: Protocol of a Randomized Controlled Trial of an Internet-Based Guided Self-Help Cognitive Behavioral Therapy Intervention - Kothari, R.; Egan, Sarah; Wade, T.; Andersson, G.; Shafran, R. (JMIR Publications, 2016)
Background: Perfectionism is elevated across, and increases risk for, a range of psychological disorders as well as having a direct negative effect on day-to-day function. A growing body of evidence shows that cognitive behavioral therapy (CBT) reduces perfectionism and psychological disorders, with medium to large effect sizes. Given the increased desire for Web-based interventions to facilitate access to evidence-based therapy, Internet-based CBT self-help interventions for perfectionism have been designed. Existing Web-based interventions have not included personalized guidance which has been shown to improve outcome rates. Objective: To assess the efficacy of an Internet-based guided self-help CBT intervention for perfectionism at reducing symptoms of perfectionism and psychological disorders posttreatment and at 6-month follow-up. Methods: A randomized controlled trial method is employed, comparing the treatment arm (Internet-based guided self-help CBT) with a waiting list control group. Outcomes are examined at 3 time points, T1 (baseline), T2 (postintervention at 12 weeks), T3 (follow-up at 24 weeks). Participants will be recruited through universities, online platforms, and social media and if eligible will be randomized using an automatic randomizer. Results: Data will be analyzed to estimate the between group (intervention, control) effect on perfectionism, depression, and anxiety. Completer and intent-to-treat analyses will be conducted. Additional analysis will be conducted to investigate whether the number of modules completed is associated with change. Data collection should be finalized by December 2016, with submission of results for publication expected in mid-year 2017. Results will be reported in line with recommendations in the Consolidated Standards of Reporting Trials Statement for Randomized Controlled Trials of Electronic and Mobile Health Applications and Online TeleHealth (CONSORT-EHEALTH). Conclusions: Findings will contribute to the literature on treatment of perfectionism, the effect of treating perfectionism on depression and anxiety, and the efficacy of Internet-based guided self-help interventions. ClinicalTrial: ClinicalTrials.gov NCT02756871; https://clinicaltrials.gov/ct2/show/NCT02756871 (Archived by WebCite at http://www.webcitation.org/6lmIlSRAa)